Aprendizagens musicais na educação infantil em escolas da rede privada de Porto Alegre : com a palavra, o professor - Ramos, Giane (2016)
This study aims to research and reflect on musical learning in Early Childhood Education as the primary objective of this dissertation. Seeking to know how these learnings happen and what is the current situation in the schools Private Network from Porto Alegre, five Music teachers were chosen, who are working at this stage of basic education, so that they could bring their impressions about these learning processes. Hence from semi-structured interviews, data were collected for analysis and conclusions. It should be noted that each person, playing a role in society, their chosen profession or one that emerged as an option, brings his or her history, beliefs, concepts of education and therefore the data collected are relevant in order to give voice to those who are directly involved in the teaching and learning processes. Children, in turn, are described by these professionals, who have the certainty of the importance of their role in the individual formation.